Traditional Business Opportunities Of Selling Cakes With Small Capital In Remboken Traditional Markets - Olviane Olke Sumampouw; Priska Mawuntu (Universitas Tarumanagara, 2020)
Traditional markets are the center of attention of many consumers when searching for products they need. The market is also a favorite place for many people to look for goods and food at cheap prices, Because in traditional markets there are lots of traders. Traditional markets are never empty of consumers. So the traditional market is a very strategic location to start a business. Selling wet and dry cakes is one of the businesses that will be appointed because after the writer saw that in the traditional market of Remboken there were those who sold wet and dry cakes but were not serious because sometimes it's available but sometimes it's also not there so many buyers are sometimes disappointed because they always fail to get these sales. This research is limited to Traditional Markets in the village of Talikuran, Remboken District. By considering the research objectives that have been set, then this research tends to use the